The Effect of Transfer Pricing and Thin Capitalization on Tax Avoidance With Profitability As A Moderating Variable - I Gusti Ayu Made Winda Maharani; Anak Agung Gde Putu Widanaputra (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Tax avoidance is a form of tax planning, which refers to the implementation of tax reduction strategies by companies through legal means due to imperfections in tax legislation. This study aims to obtain empirical evidence regarding the effect of transfer pricing and thin capitalization on tax avoidance with profitability as a moderating variable. The research was conducted on all companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2023. The sample was determined using a purposive sampling method, resulting in 127 companies, with a total of 508 observations across four (4) periods. Data collection was carried out using a non-participant observation method by accessing financial statements from the official website of the Indonesia Stock Exchange (IDX). Data were analyzed using Moderated Regression Analysis (MRA) with the SPSS application. The results show that profitability moderates by weakening the relationship between transfer pricing and tax avoidance. However, profitability does not moderate the effect of thin capitalization on tax avoidance.